페르소나 모델을 활용한 웹 기반의 V-Commerce 개발 -베트남 소비자들을 대상으로 - 정혜경; 이승민 (디지털콘텐츠학회논문지, 19(6), 2018)
본 연구는 베트남 소비자들을 대상으로 하는 동영상을 활용한 V-Commerce(비디오커머스) 웹사이트를 제작하고자 한다. 우선 베트남 소비자들의 컨텐츠 관심도나 이해도, 웹사이트 사용 목적이나 및 니즈를 파악하기 위해 설문과 심층인터뷰, 선행연구 분석 등을 실시하여 페르소나를 완성하였다. 그 결과, 첫째, 베트남인과 한국인이 바로 소통할 수 있는 창구를 만들어 상호작용이 쉽도록 한다. 둘째, 베트남인들이 관심 있어 하는 K-pop, 한국인의 패션, 한국인의 화장(혹은 화장품), 한국 음식, 한국여행, 한국어 등에 대한 다양한 정보를 제공하고 그 정보들의 카테고리를 잘 구분해서 쉽고 편하게 정보를 찾을 수 있도록 정보설계 한다. 셋째, 시청한 비디오에 나오는 상품들을 쉽게 구매까지 할 수 있도록 한다. This study aims to create a video-commerce website that uses video for Vietnamese consumers. First of all, we completed the persona by conducting understanding questionnaires, in - depth interviews, and analysis of prior research to understand the content interest and understanding of Vietnamese consumers, purpose of website use. Persona results: First, make it easy for Vietnamese and Korean people to interact with each other by creating a contact menu. Secondly, it would be provided various information about K-pop, Korean fashion, Korean makeup(cosmetics), Korean food, Korean travel, Korean, etc., which Vietnamese people are interested in. Third, it makes it easy to purchase the products that are shown in the video that they watch. KCI Citation Count: 8